Human capital and organisational outcome: mediation and moderation model - Prabandari, Sri Palupi; Masyhuri, Masyhuri; Rahmawati, Setya Ayu (Business, Management and Economics Engineering, 2025)
Purpose – This study aims to investigate organisational values as moderators and playful work design as mediators in the relationship between human capital and organisational outcomes in service industry in Indonesia, utilizing quantitative analysis. Research methodology – Purposive sampling was used to retrieve data from 305 respondents using a self-reported questionnaire. The data is analysed using the macro PROCESS using model 5. Findings – The results indicate the direct influence of human capital on organisational outcomes, mediation, playful work design, and moderation of organisational values. The findings of this study reinforce that applying high organisational values and effective human capital management can optimise organisational outcomes through playful work design. Research limitations – This research was carried out with one questionnaire distribution, future research need to conduct longitudinal studies to be known under different conditions and times in another industry. Practical implications – Manager’s must carry out digital transformation and human capital to survive and become winners amid today’s tight service industry competition by encouraging organisational values and supporting playful work design. Originality/Value – This study investigated six dimension of human capital which are suitable in the industrial era 4.0 for manager’s in service industry and its impact on organisational out- come with mediation and moderation analysis.